Hypertension and Cognitive Decline: Implications of Obstructive Sleep Apnea - Mansukhani, Meghna P.; Kolla, Bhanu Prakash; Somers, Virend K. (Frontiers in Cardiovascular Medicine, 2019)
Hypertension and dementia are highly prevalent in the general population. Hypertension has been shown to be a risk factor for Alzheimer’s dementia and vascular dementia. Sleep apnea, another common disorder, is strongly associated with hypertension and recent evidence suggests that it may also be linked with cognitive decline and dementia. It is possible that sleep apnea is the final common pathway linking hypertension to the development of dementia. This hypothesis merits further exploration as sleep apnea is readily treatable and such therapy could foreseeably delay or prevent the onset of dementia. At present, there is a paucity of therapeutic modalities that can prevent or arrest cognitive decline. In this review, we describe the associations between hypertension, dementia and sleep apnea, the pathophysiologic mechanisms underlying these associations, and the literature examining the impact of treatment of hypertension and sleep apnea on cognition. Potential areas of future investigation that may help advance our understanding of the magnitude and direction of the interaction between these conditions and the effects of treatment of high blood pressure and sleep apnea on cognition are highlighted.